Isolation and characterization of Malaysian leech saliva extract - Alaama, Mohamed (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2012)
Leech saliva contains biologically active compounds that are mainly proteins and peptides. In Malaysia leeches have been used for traditional medicine for a long time. However, there are scanty studies about the isolation and characterisation of Malaysian leeches' saliva. This study aimed to isolate and characterize leeches saliva extract. A modified and smooth extraction method of leeches' saliva without leeches' scarification is used. UV and Bradford assay protein methods showed that the saliva extract contains high concentrations of protein. RP-HPLC chromatogram revealed that more than 30 different peaks were there in leech saliva extract.. Gel electrophoresis revealed the existence of protein and peptides with different molecular weights. The gel showed up to 25 different bands. Comparison of gel electrophoresis data with protein database revealed the closeness of many molecular weights to known proteins isolated from the Hirudinaria leech family. Other proteins detected by gel electrophoresis may be related to completely new biologically active proteins and peptides or to a modification (isoforms) of the existing ones. It was observed that the period of starvation has a vital role in the concentration of saliva proteins and 12 weeks of starvation gave the highest concentration of proteins in the saliva. It was found also that 4 weeks of starvation after first feeding is enough for leeches to recover 42% of their protein concentration. Two anticoagulant proteins (protein 1 and protein 2) were isolated from leeches saliva extract by using RP-HPLC, and their molecular weights were identified (6.289kDa and 14.255kDa) respectively using tricine SDS-P AGE. These two proteins increased the thrombin time by 29 .11 % and 44.13% respectively. In addition, they inhibited the amidolytic activity of thrombin, evaluated by measuring the conversion of the chromogenic substrate (S-2238). The result showed a decrease in the conversion of the substrate (S-2238) by 30.61% and 41.22 % respectively. Traces of heavy metals concentrations were investigated in the water (natural habitat of the leeches), leeches' tissues and leeches' saliva extracts. The concentrations of heavy metals in the leeches' habitat water were found high. Hence the water specification is a class IV (INWQS). Furthermore, traces concentrations of heavy metals were found in leeches' tissues as well as in their saliva extracts. Such concentrations of heavy metals may cause health hazard, especially when leeches from such contaminated environment are applied in treatment and therapy directly without any precautions. Clearing leeches and their saliva extracts from these traces is investigated in this study. It was found that these high concentrations can be mitigated by successive replacement of the lake water by clean and non-chlorinated or distilled water for three weeks. A significant decrease for certain heavy metals concentrations was achieved depending on the type of metal. For instance in the saliva extract, undetected level of cadmium (Cd) was observed while a marginal 7.3% decrease in the case of arsenic (As) was reported after washing. In the case of leeches' tissues, the concentration of cadmium (Cd) increased unexpectedly, while a decrease of 92.38% and 20.01% in the concentration of lead (Pb) and arsenic (As) were recorded respectively.